Design and implementation of a low cost, high yield dielectric barrier discharge ozone generator based on the single switch resonant converter. Issue 8 (1st September 2013) - Salam, Zainal; Facta, Mochammad; Amjad, Muhammad; Buntat, Zolkafle
Abstract : This work proposes a low cost ozone generator which is capable of producing high ozone yield. Its dielectric barrier discharge planar‐shaped chamber is constructed using common materials; the electrodes are made of aluminium mesh and copper plate, whereas muscovite mica is used as the dielectric. The availability of thin mica sheet (< 1 mm) allows for the lowering of the initiation voltage without the use of discharge gas. The chamber is fed by a high‐voltage power supply that utilises the single switch resonant converter topology with ferrite transformer. To validate the idea, an experimental prototype ozone generator is designed and constructed. The generator is fed by a low‐voltage DC power supply (8–17 V) and does not require water or air‐cooling for its chamber. Despite its small footprint, the maximum achievable ozone yield is 120 g/kWh at 2.0 l/min, with measured efficiency of 75%. Finally, the performance of the proposed generator is critically evaluated in comparison with several important works in the same area.